Evaluation and Optimization of Asphalt Production Parameters at the Asphalt Mixing Plant in West Sumbawa - Sulaimansyah, Sulaimansyah; Wulandari, Miranti Nur; Fadli, Fadli; Wahyuni, Sri; Suhardi, Suhardi (MO.RI Publishing, 2025)
Asphalt is the main material in highway construction that plays an important role in determining the quality, durability, and comfort of road users. The demand for asphalt in Indonesia continues to increase in line with national infrastructure development, including in the West Nusa Tenggara region. PT Fima Kencana Kerthasari, located in Belo Village, Jereweh District, West Sumbawa Regency, is one of the companies engaged in the production of hot mix asphalt through a mixing plant facility. In practice, the production process often faces challenges in maintaining consistent asphalt quality due to variations in mixing temperature, inaccuracies in aggregate and asphalt measurements, and a lack of real-time process control. Considering the potential for quality improvement through the optimization of production process parameters such as temperature, mixing time, and aggregate-asphalt ratio, a systematic study at the PT Fima Kencana Kerthasari site is required. This optimization not only aims to meet technical specification standards (e.g., SNI 06-2489-1991 and SNI 7394:2008) but also to enhance the company's competitiveness through cost efficiency and operational efficiency.